Allometric relationships of the dentition of the great White Shark, Carcharodon carcharias, in forensic investigations of shark attacks - Nambiar, P.; Bridges, T.E.; Brown, K.A. (1991)
As a result of a systematic morphometric study of shark dentitions, a system of notation for describing the location of shark teeth has been developed and is proposed as a standard to be adopted for use in similar studies in the future. The macroscopic morphology of White Shark teeth has been characterised in order to gain quantitative data which might assist in identification of these sharks from bite marks on victims or objects or from shark carcasses. Using these data, a nomogram has been developed which can be used to estimate the body length of a White Shark from measurements of tooth or bite mark morphology. An example of the forensic application of such allometric data is provided as it applied to a recent fatal attack on a diver by a White Shark.